Dyglosja a proces socjalizacji - Skudrzyk, Aldona (Postscriptum Polonistyczne, 2020)
The author discusses the concept of diglossia in the sociolinguistic aspect, but also in the cognitive one, assuming the significance of the opposition between the language of primary socialisation (unofficial and spoken) and the language of secondary socialisation (official and written) for the cognitive development of an individual functioning in a situation of diglossia. A broad interpretation of the concept is supported in the paper, with the author extending it to cover also the simultaneous presence of a minority language (as the language of primary socialisation) and the general language of the dominant culture (as the language of secondary socialisation) due to the clearly separate nature of their functioning.